Determination of influencing factors for slope stability using grey relational analysis (GRA) technique - Deris A.M.; Solemon B.; Taha H.; Omar R.C. (EManuscript Technologies, 2023)
Article; factor analysis; grey relational analysis; priority journal; slope factor; statistical analysis